They Run with Surprising Swiftness : The Women Athletes of Early Modern Britain - Radford, Peter, 1939- (Book collections on Project MUSE., 2023)
"This book traces women's competitive running and participation in team sports in Britain throughout the seventeenth and eighteenth centuries"--